Abdominal Wall Granulomatous Inflammation Mimicking Malignancy on FDG PET/CT. (March 2020) - Shen, Guohua; Kuang, Anren
Abstract : Abstract: An old woman with abdominal pain complained a palpable mass on the right anterior abdominal wall. On PET/CT images, the lesion presented as a soft tissue mass with irregular shape, invading adjacent peritoneum and showing intense FDG uptake. Based on imaging findings, a malignancy was suspected, and she underwent surgical resection. However, the abdominal wall mass was diagnosed as granulomatous inflammation with a little necrosis by pathological results. Awareness of this benign disease is helpful for an accurate diagnosis of abdominal wall mass.